Exploration of Physics Concepts in Games at the Night Market - Aimmatul Afifah; Nova Allysa Qotrunnada; Kartika Septyaningrum (Indonesia Approach Education, 2021)
This study aims to show that learning physics or understanding physics concepts is not only done in the classroom, but can be done outside the classroom even at fun playgrounds. The methods used are field case studies and literature case studies. In this study, it can be concluded that learning physics or understanding physics concepts is not only done in the classroom, but can be done outside the classroom even at fun playgrounds such as the centripetal force on the Ferris wheel and merry-go-round as well as the concept of simple harmonic motion on the Kora rides. -kora. Exploration of physics concepts on game vehicles can be an innovation in learning when students are getting bored in learning physics in theory, teachers can connect physics materials and concepts with game vehicles around us or even if possible can invite students to study outside the classroom so that learning can take place. become more meaningful, fun and easy to remember by students.